The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1073/pnas.1601208113
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment enhances the genome-wide mutation rate of target cells

Abstract: Although it is well known that microbial populations can respond adaptively to challenges from antibiotics, empirical difficulties in distinguishing the roles of de novo mutation and natural selection have left several issues unresolved. Here, we explore the mutational properties of Escherichia coli exposed to long-term sublethal levels of the antibiotic norfloxacin, using a mutation accumulation design combined with whole-genome sequencing of replicate lines. The genome-wide mutation rate significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
143
4
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(180 citation statements)
references
References 89 publications
11
143
4
11
Order By: Relevance
“…Additionally, it has been postulated that specifically 8-oxo-dG, particularly in the dGTP precursor, is the main DNA lesion responsible (40). Although we did not observe the mutational fingerprint of this lesion (A·T¡C·G) as a major part of the CPR-induced spectra in the targets studied here (see also the recent study by Long and coworkers [41]), clearly reactive oxygen species (ROS) are involved in CPR mutagenesis (42). Are the mutational spectra from different bactericidal antibiotics similar?…”
Section: Discussionmentioning
(Expert classified)
“…Additionally, it has been postulated that specifically 8-oxo-dG, particularly in the dGTP precursor, is the main DNA lesion responsible (40). Although we did not observe the mutational fingerprint of this lesion (A·T¡C·G) as a major part of the CPR-induced spectra in the targets studied here (see also the recent study by Long and coworkers [41]), clearly reactive oxygen species (ROS) are involved in CPR mutagenesis (42). Are the mutational spectra from different bactericidal antibiotics similar?…”
Section: Discussionmentioning
(Expert classified)
“…Estimates of the mutation and recombination rates of Enterobacteriaceae are limited and range from 0 to 10 mutations per genome per year (38,39). These rates reflect fixed substitution rates; short-term mutation (polymorphism) rates may be higher and are known to increase under antibiotic pressure or other environmental stress (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this apparent tolerance, expression of the SOS regulon persists, suggesting a mechanism of transcriptionally responding to this signal in order to quickly adapt to changing D-serine concentrations that may be encountered (31,41). Furthermore, SOS activation can lead to an increased mutational frequency and, in turn, increase bacterial fitness after exposure to even subinhibitory concentrations of antibiotics, for example (38,39,52). Indeed, one study reported that ciprofloxacin treatment of E. coli could increase the mutation frequency by a factor of 10 4 over the spontaneous rate (53).…”
Section: Discussionmentioning
confidence: 99%
“…In the UPEC ⌬dsdA mutant, D-serine accumulation also results in a higher recA induction than that of EHEC, suggesting that this stress may account for the apparent adaptation to D-serine tolerance in EHEC. Recent studies have suggested that antibiotic-mediated mutations can not only increase resistance to antibiotics but also generally enhance the fitness of the affected bacterial cells (39,52). It was also demonstrated that after rapid adaptation, SOS expression is actually decreased, limiting further unwanted mutagenic capability (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation